Lumbar trans-spinal direct current stimulation: A modeling-experimental approach to dorsal root ganglia stimulation - Pereira, Mariana; Fernandes, Sofia Rita; Miranda, Pedro Cavaleiro; de Carvalho, Mamede (Frontiers in Neuroscience, 2022)
The excitability of spinal motor neurons (MN) can be altered through subthreshold currents, such as transcutaneous spinal direct-current stimulation (tsDCS). Current evidence shows that tsDCS can interfere with ascending somatosensory pathways and lower motor neurons’ (LMN) excitability, which points to its therapeutic potential for repairing altered spinal responses. We aim to define the best tsDCS montage for maximizing the electric field (E-field) in the lumbar spinal cord (L-SC) by computer modelling; and to apply this montage to measure the effect on LMN excitability and somatosensory evoked potentials (SSEP). A human volume conductor model was obtained from an available database. The E-field distribution was calculated considering three different electrode settings aiming at maximizing the field at L-SC and right dorsal root ganglia (DRG). The best electrode setting was then selected and applied in a blind crossover pseudo-randomized study including 14 subjects. tsDCS was delivered for 15 minutes (cathodal vs sham) over L2 vertebra level (4 mA, 144 mC/cm2), and its effect on F-waves, H-reflex (including homosynaptic depression, HD) and SSEPs was investigated in the lower limbs. All simulated montages showed higher current density and E-field magnitudes between the electrodes (> 0.15 V/m), with a major longitudinal component and with rostral-caudal direction. The induced E-field involved the sensory ganglia and was maximum in the right T8-left L2 montage, which was the one selected for the experimental protocol. We disclosed a statistically significant increase of the H-reflex amplitude at 0.1 Hz, after cathodal tsDCS on both sides. No other significant change was observed. Our results can suggest the cathodal tsDCS applied to the L- SC and DRG can modulate synaptic efficiency increasing lower motor neurons response to Ia fibers excitation. The possible implications of our findings for treating clinical conditions will be addressed in future studies.